An aptamer-targeting photoresponsive drug delivery system using "off–on" graphene oxide wrapped mesoporous silica nanoparticles. Issue 14 (18th March 2015) - Tang, Yuxia; Hu, Hao; Zhang, Molly Gu; Song, Jibin; Nie, Liming; Wang, Shouju; Niu, Gang; Huang, Peng; Lu, Guangming; Chen, Xiaoyuan
Abstract : A photoresponsive drug delivery system was developed for light-mediated drug release and aptamer-targeted cancer therapy. Abstract : We have developed a novel aptamer-targeting photoresponsive drug delivery system by non-covalent assembly of a Cy5.5-AS1411 aptamer conjugate on the surface of graphene oxide wrapped doxorubicin (Dox)-loaded mesoporous silica nanoparticles (MSN-Dox@GO-Apt) for light-mediated drug release and aptamer-targeted cancer therapy. The two "off–on" switches of the MSN-Dox@GO-Apt were controlled by aptamer targeting and light triggering, respectively. The Cy5.5-AS1411 ligand provides MSN-Dox@GO-Apt with nucleolin specific targeting and real-time indicator abilities by "off–on" Cy5.5 fluorescence recovery. The GO acts as a gatekeeper to prevent the loaded Dox from leaking in the absence of laser irradiation, and to control the Dox release in response to laser irradiation. When the GO wrapping falls off upon laser irradiation, the "off–on" photoresponsive drug delivery system is activated, thus inducing chemotherapy. Interestingly, with an increase in laser power, the synergism of chemotherapy and photothermal therapy in a single MSN-Dox@GO-Apt platform led to much more effective cancer cell killing than monotherapies, providing a new approach for treatment against cancer.